Exploring gender-based violence through creative psychosocial interventions: A qualitative study - Mouratidi, Myrto Zoi (Homo Virtualis, 2025)
This article aims to explore lived experiences related to gender-based violence through the lens of ambivalent and internalized sexism, taking into account the psychosocial dimensions of the phenomenon. Adopting a phenomenological qualitative approach, the study focuses on how individuals internalize and perpetuate gender stereotypes and ambivalent social attitudes, thereby normalizing forms of violence that often remain invisible or unacknowledged. Data were collected through semi-structured interviews supported by multimodal tools such as Dixit cards, drawings, and narrative techniques that encouraged emotional expression and reflexive dialogue. The research involved ten individual interviews with women, conducted in familiar settings to promote safety and openness. The findings revealed that participants experience sexism as an ongoing, persistent part of daily life, expressed across multiple social contexts. Everyday sexism, through small yet recurrent practices, serves as a constant reminder of the gender hierarchies that structure daily existence. Internalized sexism leads women to conform to social expectations to gain acceptance, while ambivalent sexism generates confusion by combining seemingly positive expressions with underlying inequalities. Feminism emerged as a significant concept; however, participants often avoided explicitly identifying with it due to its negative connotations and the criticism directed at those who embrace it. Overall, the findings suggest that women struggle to shed internalized stereotypes, experiencing a constant tension between their desire for empowerment and the social pressures that seek to restrict their autonomy.